The Structure of Future Teachers’ World Outlook as the Reflection of the Transformation of Social Values - Knyazeva, Tatyana N.; Povshednaya, Faina V.; Batuta, Marina B.; Lebedeva, Oksana V.; Sidorina, Elena V. (International Review of Management and Marketing, 2015)
The relevance of the subject under study is associated with the fact that social changes and economic transformations occurring in our country have caused the process of the revaluation, the reassessment of established values. In this respect, it is quite important to understand to what extent acute the contradictory tendencies of the Russian society development affect the state of the forming world outlook of the youth. The purpose of this paper is to analyze the structural-conceptual characteristics of the professional outlook of today’s students, who will be future teachers, as the reflection of the social value transformation process. The following basic methods were applied in the presented study: The Level of the Ratio of Value Importance and its Attainability Parameters in various spheres of life, The Life-Meaningful Orientations Test, The Strong-Willed Self-Control Questionnaire, the methods for studying the ability of self-regulation, which have enabled to reveal the features of valuable and volitional components in the first-year students of the Kozma Minin Nizhny Novgorod State Pedagogical University. The presented study covers the analysis of the essential characteristics of the world outlook of today’s students who will be teachers in the future. The research findings enable us to note the reduced levels of life-meaningful orientations and the general indicator of the life meaningfulness in freshmen as compared to the average-standard factors of other similar studies. In the structure of future teachers’ value orientations the socially important values are currently expulsed by orientation targets of individualistic nature. The study of a conative component of the future teachers’ world outlook, which determines the direction of the person’s behaviour, testifies the decreasing social activity of the youth, poorly expressed willed readiness to act in accordance with public values. The obtained results give a clear evidence of the available problem of the first-year students’ professional identification, the non-formed value-meaningful attitude towards the profession of a teacher. Keywords: world outlook, value orientations, life-meaningful orientations, a conative component of world outlook, students-future teachers. JEL Classifications: A20, 031, 035